Infertility, Assisted Reproductive Technologies and Hormone Assays 2019
DOI: 10.5772/intechopen.81653
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Oocytes and Embryos: Current Status and Opportunities

Abstract: The biochemical and metabolic activities of living cells are virtually stopped at ultralow temperature and they enter into a suspended state of animation. However, as such, exposure of living cells to ultralow temperature is associated with complex changes that reduce their survivability following freeze-thawing. Cryopreservation is the method for preserving living cells at ultralow temperature at genetically and physiologically stabilized state. Cryopreservation of oocytes and embryos is an integral part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
(71 reference statements)
1
8
1
Order By: Relevance
“…This highlights the fact that both genders are interested in reproduction and childbearing. This finding was in contrast to a previous study by Tschudin and Bitzer (2009), who reported that women were more interested in fertility preservation than men [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This highlights the fact that both genders are interested in reproduction and childbearing. This finding was in contrast to a previous study by Tschudin and Bitzer (2009), who reported that women were more interested in fertility preservation than men [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Fertility preservation is usually defined as a process of preserving reproductive cells including oocytes, sperm, and embryos, or reproductive tissues including ovarian and testicular tissues to enable individuals to start a family at a time of their choice when their fertility is compromised [ 30 ]. The main objective of fertility preservation intervention is to minimize the primary disease burden and more importantly to ensure maintaining or preserving the reproductive health [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the cryopreservation of oocytes, vitrification offers an alternative to the standard slow freezing with many advantages such as simplicity, cost-effectiveness, and quickness (Mochida & Ogura, 2010). Vitrification has become the routine method for oocyte cryopreservation in human (Arindam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For the cryopreservation of oocytes, vitrification offers an alternative to the standard slow freezing with many advantages such as simplicity, cost‐effectiveness, and quickness (Mochida & Ogura, 2010). Vitrification has become the routine method for oocyte cryopreservation in human (Arindam et al, 2018). Oocyte vitrification has numerous applications in many animal species, such as cattle (Hamano et al, 1992), rabbit (Al‐Hasani et al, 1989), horse (Maclellan et al, 2002), and pigs (Somfai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gamete cryopreservation has achieved a great progress during the last five decades. It provides valuable sperm and oocytes and accelerates the dissemination of genetic materials and ensure providing continuous source of oocytes and embryos for many applications in genetic improvement programs; in vitro embryo production, embryo transfer (Dhali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%